REFLECTIVE-BASED ACADEMIC SUPERVISION BY SCHOOL PRINCIPALS: A STRATEGY FOR IMPROVING TEACHERS’ PEDAGOGICAL COMPETENCE IN PUBLIC ELEMENTARY SCHOOLS - Samsu Samsu; Try Susanti; Fransisko Chaniago; Edi Saputra (Jurnal Manajemen Pendidikan, 2026)
This study aims to provide an in-depth analysis of the implementation of reflective-based academic supervision in improving teachers’ pedagogical competence at SD Negeri 107 Air Mumu, Kerinci Regency. The limited practice of self-evaluation in the use of diverse teaching methods became the main concern underlying the application of this supervisory approach. The study employed a qualitative approach with a case study design to explore the phenomenon of supervision based on the actual conditions found in the field. Data were collected through participatory observation, in-depth interviews, and documentation studies involving the school principal and teaching staff. Data validity was ensured through technique and source triangulation, while data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that reflective-based academic supervision was carried out through five systematic stages: identifying teachers’ needs, observing classroom learning activities, conducting post-observation reflective dialogue, providing constructive feedback, and offering continuous clinical assistance. This reflective approach proved effective in encouraging teachers to independently evaluate their weaknesses, develop new instructional strategies, and improve classroom teaching practices without feeling judged. The implementation of this supervision model not only enhanced teachers’ pedagogical competence.